The Effect of Percentage Composition of Briquettes Randu Fruit Husk Charcoal and Rice Husk on Calorific Value and Burning Rate - Yogi Harti Ningrum; Dwi Pangga; Sukainil Ahzan; Habibi; Imam Sya’roni (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: This study is to determine the effect of the percentage composition of briquettes made from kapok fruit husk charcoal (AKBR) and rice husk (ASP) on calorific value and burning rate. Method: This research is an experimental study conducted in the Physics Laboratory of FSTT Undikma. The research design was carried out in four stages: preparing tools and materials, the carbonization process, briquette production, and briquette testing. Result: The results of the study on briquettes made from AKBR and ASP showed that the highest calorific value was obtained with a composition of 90% AKBR + 0% ASP, reaching 8,632 calories. Meanwhile, the lowest calorific value was recorded at a composition of 0% AKBR + 90% ASP, amounting to 7,428 calories. Novelty: The optimal burning rate was observed at a composition of 90% AKBR + 0% ASP, achieving 0.57 grams/minute, whereas the lowest burning rate was found at a composition of 0% AKBR + 90% ASP, with a value of 0.39 grams/minute.